Urinary excretion profiles of 11-nor-9-carboxy-Δ 9-tetrahydrocannabinol : Study III. A Δ 9-THC-COOH to creatinine ratio study - Fraser, Albert D.; Worth, David (Forensic science international, 2003)
Huestis and Cone reported in [J. Anal. Toxicol. 22 (1998) 445] that serial monitoring of Δ 9-THC-COOH/creatinine ratios in paired urine specimens collected at least 24 h apart could differentiate new drug use from residual Δ 9-THC-COOH excretion following acute marijuana use in a controlled setting. The best accuracy (85.4%) for predicting new marijuana use was for a Δ 9-THC-COOH/creatinine ratio ≥0.5 (dividing the Δ 9-THC-COOH/creatinine ratio of specimen no. 2 by the specimen no. 1 ratio). In previous studies in this laboratory [J. Anal. Toxicol. 23 (1999) 531 and Forensic Sci. Int. 133 (2003) 26], urine specimens were collected from chronic marijuana users ≥24 h or ≥48 h apart in an uncontrolled setting. Subjects with a history of chronic marijuana use were screened for cannabinoids with the EMIT ® II Plus cannabinoids assay (cut-off 50 ng/ml) followed by confirmation for Δ 9-THC-COOH by GC–MS (cut-off 15 ng/ml). Creatinine was analyzed as an index of dilution. The objective of the present study was to evaluate whether creatinine corrected specimens could differentiate new marijuana or hashish use from the excretion of residual Δ 9-THC-COOH in chronic marijuana users based on the Huestis 0.5 ratio. Urine specimens ( N=376) were collected from 29 individuals ≥96 h between urine collections. The mean urinary Δ 9-THC-COOH concentration was 464.4 ng/ml, mean Δ 9-THC-COOH/creatinine ratio (ng/(ml Δ 9-THC-COOH mmol l creatinine)) was 36.8 and the overall mean Δ 9-THC-COOH/creatinine ratio of specimen 2/mean Δ 9-THC-COOH/creatinine ratio of specimen 1 was 1.37. The Huestis ratio calculation indicated new drug use in 83% of all sequentially paired urine specimens. The data were sub-divided into three groups (Groups A–C) based on mean Δ 9-THC-COOH/creatinine values. Interindividual mean Δ 9-THC-COOH/creatinine values ranged from 4.7 to 13.4 in Group A where 80% of paired specimens indicated new drug use ( N=10) and 20.4–39.6 in Group B where 83.6% of paired specimens indicated new drug use ( N=7). Individual mean Δ 9-THC-COOH/creatinine values ranged from 44.2 to 120.2 in Group C where 84.5% of paired urine specimens indicated new marijuana use ( N=12). Correcting Δ 9-THC-COOH excretion for urinary dilution and comparing Δ 9-THC-COOH/creatinine concentration ratios of sequentially paired specimens (collected ≥96 h apart) may provide an objective indicator of ongoing marijuana or hashish use in this population.